Factors affecting acceptance of e-marketplace among small and medium-sized entreprises (SMEs) in Kota Bharu, Kelantan - Deavisri Paramesvaran; Eqhmal Hakimi Zainodin; Nabila Ashiqin Zulkifli; Nur Syuhada Zainol (2023)
This research aims to identify factors affecting acceptance of E-Marketplace. The emerge of COVID-19 has transform the business pattern for surviving in the pandemic era. E-Marketplace is one of the platforms that SMEs can use for promoting their businesses. Therefore, the factors that affect the acceptance of E-Marketplace among SMEs in Kota Bharu, Kelantan will be the main objective of this study. This research focus on the relationship between the factors and acceptance of E-Marketplace, specifically how the potential factor can influence intention of SMEs to accept E-Marketplace as their new business platform. To achieve the objectives of this study, quantitative methods were conducted using Google Forms as instrument. The population for this study was 1,900 in Kota Bharu, Kelantan and collected data of 320 SMEs owners as sample size. Additionally, the statistical analyses were performed with SPSS, and the results were gathered using descriptive analysis, validity and reliability test, regression analysis also Pearson correlation coefficient. Perceived usefulness, perceived ease of use, attitude, subjective norm and perceived behaviour control, the factor are known will affect the acceptance of E-Marketplace among SMEs in Kota Bharu, Kelantan.